Runaway world : how globalisation is reshaping our lives - Giddens, Anthony (Profile Books, 2002)
Before the current global era it is impossible to imagine that comparable events [like September 11] could have occurred, reflecting as they do our new-found interdependence. The rise of global terrorism, like world-wide networks involving in money-laundering, drug-running and other forums of organised crime, are all parts of the dark side of globalisation.' From the new Preface This book is based on the highly influential BBC Reith lecture series on globalisation delivered in 1999 by Anthony Giddens. Now updated with a new chapter addressing the post-September 11th global landscape, this book.